Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam (IPA) dengan Metode Pembelajaran Mind Map - Heri Riswanto; Dasmo Dasmo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2015)
. The purpose of this research to analize the influence mind map method concerning the result of studying science with controling the student’s ability in the beginning. This research used experiment method with analize ANAKOVA. The sample which is used for this research are the students in VIII SMP with 60 students which spread in VIII.E and VIII.F class of SMPN 275 Jakarta. The results of this research are: First, controlling influence the students’ ability in the beginning, there is difference result of studying science which is significant between the students who study by using mind map method and using conventional method. (Fhitung = 12,01 > Ftabel = 4,01) Second, controlling influence the students’ ability in the beginning, the result of study science, The students who study by using mind map method is better than using conventional method (thitung = 3,345 > ttabel = 1,672).